FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SIKAP REMAJA TERHADAP PERILAKU SEKSUAL PRANIKAH DI KECAMATAN SIBERUT SELATAN, KEPULAUAN MENTAWAI TAHUN 2018 - Rennie Yolanda; Angela Kurniadi; Tommy Nugroho Tanumihardja (Puslitbang Upaya Kesehatan Masyarakat, 2019)
Abstract Background: Increasing percentage of adolescents who have had premarital sex from year to year and many factors that associated with adolescent attitudes towards premarital sexual behavior. Objective: Identifies factors associated with adolescent attitudes towards premarital sexual behaviour in South Siberut. Method: Observational analytic research with a cross-sectional study. Respondents were collected from all high schools in South Siberut using stratified random sampling with a total of 126 respondents. Variables included are gender, father’s education level, mother’s education level, parent income, HIV/AIDS knowledge, and attitude towards HIV/AIDS. Research instrument using questionnaires. Data were analyzed using Chi-square test. Result: 53,2 percent of adolescents had an attitude that didn’t support premarital sexual behaviour. The result of bivariate analysis showed that there was a relationship between adolescent attitudes towards premarital sexual behaviour with gender (p=0,003). There was no relationship between adolescent attitudes towards premarital sexual behaviour with father’s education level (p=0,161), mother’s education level (p=0,915), parent income (p=0,69), HIV/AIDS knowledge (p=0,257), and attitude towards HIV/AIDS (p=0,141). Conclusion: Factor that associated with adolescent attitudes towards premarital sexual behaviour is gender. Father’s education level, mother’s education level, parent income, HIV/AIDS knowledge, and attitude towards HIV/AIDS aren’t associated with adolescent attitudes towards premarital sexual behaviour. Keywords: premarital sexual behaviour, HIV/AIDS, adolescent, South Siberut. Abstrak Latar belakang: Meningkatnya persentase remaja yang telah melakukan hubungan seksual pranikah dari tahun ke tahun dan banyaknya faktor yang berhubungan dengan sikap remaja terhadap perilaku seksual pranikah. Tujuan: Mengidentifikasi faktor-faktor yang berhubungan dengan sikap remaja terhadap perilaku seksual pranikah di Kecamatan Siberut Selatan. Metode: Penelitian analitik observasional dengan studi potong lintang. Responden berasal dari seluruh SMA/sederajat di Kecamatan Siberut Selatan dengan pengambilan sampel acak berstrata sejumlah 126 responden. Variabel yang dicari meliputi jenis kelamin, tingkat pendidikan ayah, tingkat pendidikan ibu, penghasilan orangtua, tingkat pengetahuan HIV/AIDS, dan sikap terhadap HIV/AIDS. Instrumen penelitian menggunakan kuesioner. Analisis data dengan uji kai kuadrat. Hasil: Sebanyak 53,2 persen remaja memiliki sikap tidak mendukung perilaku seksual pranikah. Hasil analisis bivariat menunjukkan bahwa terdapat hubungan antara sikap remaja terhadap perilaku seksual pranikah dengan jenis kelamin (p=0,003). Tidak terdapat hubungan antara sikap remaja terhadap perilaku seksual pranikah dengan tingkat pendidikan ayah (p=0,161), tingkat pendidikan ibu (p=0,915), penghasilan orangtua (p=0,69), tingkat pengetahuan HIV/AIDS (p=0,257), dan sikap terhadap HIV/AIDS (p=0,141). Kesimpulan: Faktor yang berhubungan dengan sikap remaja terhadap perilaku seksual pranikah adalah jenis kelamin. Tingkat pendidikan ayah, tingkat pendidikan ibu, penghasilan orangtua, tingkat pengetahuan HIV/AIDS, dan sikap terhadap HIV/AIDS tidak berhubungan dengan sikap remaja terhadap perilaku seksual pranikah. Kata kunci: perilaku seksual pranikah, HIV/AIDS, Remaja, Siberut Selatan